EVALUASI LAYOUT DESIGN UNTUK MENINGKATKAN PENJUALAN PADA TOKO SM-SHOP-ONLINE DI JAKARTA - Wijaya, Andi; Jennie Jane; Budiman, Bellinda (Lembaga Penelitian dan Pengabdian Kepada Masyarakat Universitas Tarumanagara, 2024)
Layout design has a very strategic impact on stores, because effective layout can help organizations achieve strategies that support low costs and differentiation. Arranging the layout design in each online shop is a problem that is often encountered and this is not easy to avoid, even on a simpler scale. Efficiency will be created in online sales stores if the display arrangements are well planned. The benefit that will be achieved in this activity is that the layout design in the SM-Shop-Online store is used to make it easier to pick up or search for products so that it meets consumer expectations which in conclusion can increase sales. The PKM program implemented is in the form of determining the layout of the SM-Shop-Online shop, because so far the layout in this shop is not good and is still not neatly arranged. Through a good layout, it is hoped that it will be easier for consumers to find the goods they need so that they can increase sales. Tarumanagara University as a campus entrepreneur helps provide funds to carry out this community service activity.